2012
DOI: 10.1016/j.jpsychires.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential relationships of impulsivity or antisocial symptoms on P50, N100, or P200 auditory sensory gating in controls and antisocial personality disorder

Abstract: Limited information is available on the relationship between antisocial personality disorder (ASPD) and early filtering, or gating, of information, even though this could contribute to the repeatedly reported impairment in ASPD of higher-order information processing. In order to investigate early filtering in ASPD, we compared electrophysiological measures of auditory sensory gating assessed by the paired-click paradigm in males with ASPD (n = 37) to healthy controls (n = 28). Stimulus encoding was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
4
22
0
Order By: Relevance
“…We based this hypothesis on the assumption that the different MLAER components reflect different, albeit related, underlying mechanisms and functions (Boutros et al, 2004a; Brockhaus-Dumke et al, 2008; Crowley and Colrain, 2004; Lijffijt et al, 2012; Lijffijt et al, 2009). Sensory gating is a multistage process, and the different MLAER gating indices are not redundant measures of sensory gating mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We based this hypothesis on the assumption that the different MLAER components reflect different, albeit related, underlying mechanisms and functions (Boutros et al, 2004a; Brockhaus-Dumke et al, 2008; Crowley and Colrain, 2004; Lijffijt et al, 2012; Lijffijt et al, 2009). Sensory gating is a multistage process, and the different MLAER gating indices are not redundant measures of sensory gating mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory gating is a multistage process, and the different MLAER gating indices are not redundant measures of sensory gating mechanisms. Indeed, P50 is thought to reflect pre-attentional processes, N100 is associated with attentional triggering, particularly to irrelevant information, and P200 is associated with orienting and allocation of attention (Lijffijt et al, 2012; Náátánen, 1992). We found that the correlates of P50 gating were not the same as the correlates of N100 and P200 gating.…”
Section: Discussionmentioning
confidence: 99%
“…Once the stimulus is detected, attention may (or may not) be allocated to it, and this process has been related to P200 amplitude. Furthermore, impulsivity (Lijffijt et al, ) as well as expression style of angry feelings (measured by the Anger Expression Inventory, Stewart et al, ), positively correlated with N100 amplitude. Moreover, findings have shown that frontocentral P200 was larger for wins (indicated by positive feedback), compared to losses (indicated by negative feedback).…”
mentioning
confidence: 99%
“…P50 auditory sensory gating measures P50 amplitude suppression following presentation of the same auditory stimulus in short temporal proximity, reflecting pre-attentional information filtering (95)(96)(97)(98). P50 gating is impaired in PTSD compared to trauma controls (99), and after acute stress in healthy individuals (100,101).…”
Section: Biomarkers Of Nmdar Target Engagementmentioning
confidence: 99%